Síntese da SBA-15 e [Al]-SBA-15 com diferentes ácidos: efeito nas propriedades texturais e estruturais - Iga, Gustavo Duran (Universidade Federal de São Carlos, 2021)
The development of new heterogeneous catalysts is of fundamental importance to expand their applicability and enable a sustainable future. For this, varying synthesis parameters of those catalysts it is a fundamental study that can provide a better understanding and control of structures. In this scenario, after the great discovery of mesoporous silicas of the M41S family, the SBA-15 molecular sieve emerged, which presented several structural advantages over the predecessor materials. Only few studies do the variation of the acid source in this synthesis, and this introduces other species of counterion into the reaction medium, thus this could generate interesting’s structural properties. The interaction of anions with amphiphilic molecules are given by the Hofmeister tendency of the anions. Therefore, the present work aims to investigate the effect of the counterion from the textural and structural properties of SBA-15 materials. The results showed that the conjugated base from the acid source affects the structural properties in diverse ways. In general, it was noted that the greatest structural effect promoted by salting-in anion acids (NO3-, Br-) were the most compact structures, and salting-out anions (HSO4- and Cl-) promoted larger pores and better ordered materials, possibly due to the effect of the counterion on the micelles according to the Hofmeister series, following the ability of each anion to hydrate. It was observed that the synthesis with HNO3 has a greater potential for functionalization and that with HBr may have higher hydrothermal resistance, enabling more specific applications to these mesoporous silicas. The counterion effect on the synthesis of [Al]-SBA-15 were also investigated, and an efficient new synthesis methodology was developed. The materials demonstrated distinctions only by structural and textural properties. In this sense, as the catalytic activity and the preliminary results of acidity did not show great differences between the materials, the synthesis of SBA-15 and [Al]-SBA-15 can be reformulated for the use of H2SO4, a cheaper acid that has advantages over the standard synthesis with HCl, which presented residual chloride in the structure of pure SBA-15.
Synthesis of SBA-15 and [Al]-SBA-15 with different acids: effect on textural and structural properties
Keywords: Sílicas mesoporosas; Efeito do contraíon; Variação do ácido; Aluminossilicato; Peneiras moleculares; Hofmeister; SBA-15; Mesoporous Silica; Counterion effect; Aluminosilicate; Molecular sieves; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA